Gender and Aging in the Bangkok Metropolitan Area - Prachuabmoh, Vipan (World Bank, Washington, DC, 2022)
The purpose of this study is to assess the differences between older men and women (aged sixty and above) residing in the Bangkok Metropolitan Area in order to better understand gender disparities and inform policies and programs for the aged. An analysis of the demographic attributes of older persons in the Bangkok Metropolitan Area (BMA) revealed that over 50 percent of the older population are "young-old" (between 60-69 years old), while approximately 12 percent are "oldest-old" (80 years old or more). There is a higher percentage of older women in the oldest-old group, likely due to the fact that women have a longer lifespan than men. This imbalance is a cause for concern as older women have a higher probability of being dependent, both financially and health-wise.